2003
DOI: 10.1177/000348940311200611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Sex, and Disorder on Voice Range Profile Characteristics of 230 Children

Abstract: In this study, the effect of age, sex, and disorder on the vocal performance of 230 children 6 to 11 years of age was investigated by means of the voice range profile (VRP). Ninety-four control children and 136 children with disorders were studied. The VRPs were quantitatively described by frequency and intensity characteristics, as well as by morphological characteristics. Significant differences between healthy children and children with disorders were found. Age has a different effect in girls than in boys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
13

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 22 publications
1
10
0
13
Order By: Relevance
“…A fonetografia é capaz de registrar todas as possibilidades laríngeas em relação à frequência e à intensidade sonora, uma vez que abrange os sons mais agudos e mais graves que a laringe humana é capaz de produzir e as maiores e menores intensidades envolvidas na emissão de uma vogal (3,4,7,19) . Poucos são os estudos voltados para a obtenção de parâmetros de normalidade para falantes do Português Brasileiro.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A fonetografia é capaz de registrar todas as possibilidades laríngeas em relação à frequência e à intensidade sonora, uma vez que abrange os sons mais agudos e mais graves que a laringe humana é capaz de produzir e as maiores e menores intensidades envolvidas na emissão de uma vogal (3,4,7,19) . Poucos são os estudos voltados para a obtenção de parâmetros de normalidade para falantes do Português Brasileiro.…”
Section: Discussionunclassified
“…As medidas de todas as frequências apresentadas na abscissa do fonetograma obtidas pelo VRP na fonetografia (Figura 1) foram convertidas de Hertz para semitom, a fim de permitir a realização do cálculo da área do fonetograma, por ser o semitom uma medida linear e apresentar intervalos regulares em escala musical de 12 semitons, o que não ocorre com o Hz, que é uma medida exponencial. Além disso, os valores de extensão vocal na literatura vêm sendo utilizados em semitons (4,7,9,10,(15)(16)(17)(18) , possibilitando comparações posteriores.…”
Section: Métodosunclassified
See 1 more Smart Citation
“…The phonetography is a measure capable of recording all laryngeal possibilities regarding the frequency and vocal intensity, as it covers sounds more acute and severe that the human larynx is able to produce and the highest and lowest intensities generated during the emission of a vowel 2,13,24,25 . Despite the importance of the exam, no studies were found related to the reference values of the voice range profile in Brazilian Portuguese speakers without voice disorders in the young-adult age group, with dentofacial balanced conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The exam started in C 3 (dó 3 The measures from all frequencies given in the abscissa of the phonetogram obtained by VRP in the phonetography ( Figure 1) were converted from Hertz to semitone in order to allow the calculation of the phonetogram area, for being the semitone a linear measure which presents regular intervals in musical scale in 12 semitones, which does not occur with Hertz, which is an exponential measure. Moreover, the values of the vocal range in the literature have been used in semitones 5,8,13,23,24 , enabling later comparisons.…”
Section: Introductionmentioning
confidence: 99%